An assessment by nurses and mothers of a 'road-to-health ' book in the Western Cape - D Harrison; H Harker; Hde V Heese; MD Mann (AOSIS, 2005)
Objectives: To evaluate English, Afrikaans, and Xhosa mother-retained 'Road-to- Health Book' (RTH book) for children, and an electronic calculator. Design: Researchers D Harrison (DH) and H Harker (HH) informed clinic staff about the contents and significance of the RTH book. They requested nurses to use this book in conjunction with the Road-to-Health Card and to issue and explain its use to every visiting client. The use of an electronic calculator that plotted horizontal centile and Z-score charts was demonstrated and explained. To determine the relevance of the book and the electronic calculator, nurses involved in the study for 6 months were given three standardised descriptive questionnaires with 'yes', 'no' and 'don't know' responses. Clients were traced and interviewed by the researchers after 6 -1 2 months to obtain their views on the book. Setting: Clinics that provided children with healthcare in 24 locations in the Western Cape Province participated in the study. The children lived in informal settlements, in low-, middle- and high-income residential areas, and on farms in the Cape Town. Stellenbosch, and Paarl regions. Subjects: One hundred and fourteen nurses were enrolled in the study as well as 581 clients to whom the RTH book was issued. Outcome measures: The use of and comments on the RTH book by nurses and clients were based on analysis of the questionnaires. Results: The majority of nurses (81.6%) and clients (96%) found the RTH book useful. The horizontal and Z-score growth charts and electronic calculator were less acceptable because their use was time-consuming and less well understood. Conclusion: The RTH book with appropriate modifications should be issued to clients in place of the current Road-to-Health card and educational material.